The Translational Body: Theatre Translation and Interpretation in Brazilian Sign Language (Libras) - Celina Nair Xavier Neta; Rachel Louise Sutton-Spence (Cadernos de Tradução, 2023)
This article introduces and develops the concept of the “translational body” as a construct in the process of translation and interpretation of Brazilian Sign Language (Libras), describing its relationship with the system of theatre. We show that Libras/Portuguese interpreters (TILSP) working in theatre settings are creative, political and artistic agents, with professional, didactic and activist profiles, all of which contribute to the polysystem created in Libras theatre translation. We argue that the translational body is a multiple, organic, procedural, dynamic and dialogic construct and that its presence in the theatrical polysystem organises, challenges and brings together the linguistic and cultural repertoires of theatre in new ways. Interviews conducted with TILSPs working in theatre, theatre producers and deaf audience members were analysed, drawing on Even-Zohar's Theory of Polysystems (2018) together with Embodiment Theory and existing Brazilian research by Silva Neto (2017), Fomin (2018), Resende (2019), Rigo (2019) and Albres and Santos (2020). We show that the process of Libras translation and interpretation in theatre is a process of construction of a body which is presented with the actors on stage and which incorporates translation in its relationship with the different systems that form part of the theatrical polysystem.